The effects of Qalb with Tawhidic paradigm in strategic planning of higher education institutions - Mhd. Sarif, Suhaimi (PIMM Experts Sdn Bhd, 2018)
Strategic planning of higher education institutions requires balanced, holistic and entrepreneurial dimensions for sustainable performance. The presence of Malaysia Education Blueprint 2016- 2025 (Higher Education) together with its major playbooks enables higher education institutions in Malaysia to achieve its vision, mission, and goals. The Qalb-component in leadership reinforces the commitment with drive, focus, energy and synergy of higher education institutions with consistency, resilience and perseverance. The personal interview with project managers of higher education institutions argued that qalb-leadership with Tawhidic paradigm enables greater engagement with the stakeholders for profitable and sustainable relationship with internal and external stakeholders. In the Industry 4.0 and Society 5.0 environments with soul and qalb are essential to allow for greater human connection, interaction, and engagement. The informants suggested qalb-ecosystem is necessary to reinforce the qalb-driven leadership into higher education institutions. The effects of Qalb with Tawhidic paradigm are apparent at the strategy formulation, implementation and evaluation. The dynamic business market induces complexity and difficult to the strategists to comprehend the external factors as part of formulating strategies for the future. The qalb-component is embedded in intuitive decision making process to make sense of the present environment before forecasting for the future. The informants suggested strategists to increase qalb reliability with dialog or focused group study with key stakeholders.